The impact of social capital and social support on the health of female-headed households: a systematic review - Somayyeh Khazaeian; Nourossadat Kariman; Abbas Ebadi; Malihe Nasiri (Electronic Physician, 2017)
Background and aim: Social capital and social support as determinants of health play an important role in the health of female heads of households. Considering the increasing number of female-headed families in Iran and the world, this study was conducted to systematically review the impact of social capital and social support on the health of female heads of households. Methods: This study was conducted as a systematic review in September 2016. Its data were collected from available papers in different databases including Iranmedex, Magiran, Scientific Information Database (SID), Irandoc, Scopus, Science Direct, PubMed and Google Scholar. Using advanced search, all published papers from 2000 to 2015 with full text were selected using related keywords. After reviewing by browsers and adapting to the inclusion and exclusion criteria, 15 papers were entered into the study. The Strengthening the Reporting of Observational Studies in epidemiology (STROBE) checklist was used to evaluate the quality of papers. Results: Based on the findings of these studies, there was a significant relationship between social capital and its components (trust, sense of belonging and social participation) as well as all aspects of health. Additionally, social support and its dimensions (emotional, instrumental and informational) affected health; however, among these dimensions, instrumental support of a stronger predictor was concerned with health, especially mental health. Conclusion: Social factors such as social capital and social support are effective on human health, particularly health of female-headed households, since they affect proactive identity and increase information resources, collaboration as well as collective decisions and actions. Furthermore, they provide emotional and instrumental support to group members and prevent further health problems